Implementasi Metode ARAS dalam Penentuan Kelayakan Pemberian Kredit Pemilikan Rumah (KPR) - Guswandi, Dodi; Hafizh, M; Wahyuni, Suci; Novita, Triana (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
A house is a primary need that everyone must have, yet not everyone can afford to purchase it outright. Therefore, a bank is needed as a financial institution to provide financial assistance through credit disbursement. Bank Syariah Indonesia (BSI) offers several Home Ownership Credit (HOC) programs with the Murabahah sale and purchase contract. The current analysis of eligibility determination for granting KPR credit at Bank BSI does not yet utilize an appropriate method for decision-making. This study aims to design a Decision Support System (DSS) using the Additive Ratio Assessment (ARAS) method to assist Bank BSI in analyzing KPR customer data quickly, accurately, and precisely. The ARAS method focuses on comparison with an ideal solution, ensuring that the best alternative approaches optimal conditions based on the specified criteria. The results of this study can help Bank BSI determine the eligibility of KPR credit disbursement more effectively, and the system can rank customer data as eligible or not eligible based on predefined value thresholds.